Sex differences in metabolic and adipose tissue responses to juvenile-onset obesity in sheep - Bloor, Ian D.; Sébert, Sylvain P.; Saroha, Vivek; Gardner, David S.; Keisler, Duane H.; Budge, Helen; Symonds, Michael E.; Mahajan, Ravi P. (Endocrine Society, 2013)
Sex is a major factor determining adipose tissue distribution and the subsequent adverse effects of obesity-related disease including type 2 diabetes. The role of gender on juvenile obesity and the accompanying metabolic and inflammatory responses is not well established. Using an ovine model of juvenile onset obesity induced by reduced physical activity, we examined the effect of gender on metabolic, circulatory, and related inflammatory and energy-sensing profiles of the major adipose tissue depots. Despite a similar increase in fat mass with obesity between genders, males demonstrated a higher storage capacity of lipids within perirenal-abdominal adipocytes and exhibited raised insulin. In contrast, obese females became hypercortisolemic, a response that was positively correlated with central fat mass. Analysis of gene expression in perirenal-abdominal adipose tissue demonstrated the stimulation of inflammatory markers in males, but not females, with obesity. Obese females displayed increased expression of genes involved in the glucocorticoid axis and energy sensing in perirenal-abdominal, but not omental, adipose tissue, indicating a depot-specific mechanism that may be protective from the adverse effects of metabolic dysfunction and inflammation. In conclusion, young males are at a greater risk than females to the onset of comorbidities associated with juvenile-onset obesity. These sex-specific differences in cortisol and adipose tissue could explain the earlier onset of the metabolic-related diseases in males compared with females after obesity.